Interação de fatores bióticos e abióticos na ocorrência de Damping-off em milho e feijoeiro - Gomes, Delineide Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The objective of the research was to determine the influence of biotic and abiotic factors on the occurrence of damping-off of pre and post - emergence, and others problems to the seeds and seedlings, when the sowing of corn and bean. They chose two plots of corn and bean, growing season 2007/2008, from the cultivars Carioca and D 766 respectively, according to his distinction in high and low vigour, low fungi incidence and absence of Rhizoctonia solani. Disinfested seeds were infected with the fungus in culture medium without BDA and water restriction (mannitol, -1.0 MPa). In control treatments was the same growing medium, but without the presence of the fungus. For each treatment the seeds were superimposed in culture media for 36 hours for the corn and bean for 20 hours. For the direct addition of the fungus in soil, we used the technique of sterile sorghum seeds. The experiment was conducted in two different seasons (hot and cold). For two growing seasons the plots were established in plastic pots (capacity 4.5 L) containing sterilized soil prepared according to the randomization of treatments in a greenhouse. The treatments were made from three water availability in the soil contained in vase (30 %, 50 % and 70 % retention of water), two levels of vigour of the seed (high and low vigour) with and without inoculation of Rhizoctonia solani by of inoculation in the seed of the host and soil addition with sterile sorghum seeds. Were four replicates, each containing two vessels, totaling eight pots for each treatment. Twenty days after inoculation, for the cold season, and fifteen days for the hot season was to assess the severity, damping-off of pre and post-emergence, seedling length, dry matter weight and percentage of seedlings healthy.

O objetivo da pesquisa foi determinar a influência de fatores abióticos e bióticos sobre a ocorrência de “damping-off” de pré e de pós – emergência, além de outros danos nas sementes e plântulas, quando da semeadura de milho e feijão. Foram escolhidos dois lotes de milho e feijão, safra 2007/2008, provenientes das cultivares D 766 e Carioca, respectivamente, de acordo com sua distinção em alto e baixo vigor, com baixa incidência fúngica e ausência de Rhizoctonia solani. Sementes desinfestadas foram infectadas com o fungo em meio de cultura BDA com restrição hídrica (acrescido de manitol a -1,0 MPa). Nos tratamentos testemunha foi utilizado o mesmo meio de cultura, porém, sem a presença do fungo. Para cada tratamento as sementes foram sobrepostas nos meios de cultura por 36 horas para o milho e por 20 horas para o feijão. Para a infestação direta do fungo em solo, foram utilizadas sementes de sorgo esterilizadas. O experimento foi conduzido em duas épocas distintas (caracterizadas como fria e quente). Para as duas épocas, as parcelas experimentais foram constituídas de vasos plásticos (capacidade de 4,5 L) contendo terra esterilizada dispostos segundo a casualização dos tratamentos em casa de vegetação. Os tratamentos foram constituídos a partir de três disponibilidades hídricas no solo contido em vaso (30 %, 50 % e 70 % de retenção de água), dois níveis de vigor da semente (alto e baixo vigor) com e sem a inoculação de Rhizoctonia solani, através de inoculação na própria semente do hospedeiro e da infestação no solo através de sementes de sorgo esterilizadas. Foram feitas quatro repetições, cada uma contendo dois vasos, totalizando oito vasos para cada tratamento.
Keywords: Sementes; Germinação; Temperatura; Epígea; Hipógea; Vigor; Disponibilidade hídrica no solo; Epigeous; Hypogeal; Rhizoctonia solani; Vigour; Water availability